LACTATE DEHYDROGENASE A (LDHA) IRNA COMPOSITIONS AND METHODS OF USE THEREOF - ERBE, David; KNIGHT, John; LIEBOW, Abigail; HINKLE, Gregory; WOOD, Kyle, David; HOLMES, Ross, Philip; FITZGERALD, Kevin (2020)
The invention relates to double-stranded ribonucleic acid (dsRNA) compositions targeting the LDHA gene, as well as methods of inhibiting expression of LDHA, methods of inhibiting LDHA and HAO1, and methods of treating subjects that would benefit from reduction in expression of LDHA, such as subjects having an oxalate pathway-associated disease, disorder, or condition, using such dsRNA compositions.